STABILISASI TANAH DENGAN MENGGUNAKAN PASIR DAN ABU SERABUT KELAPA TERHADAP NILAI CBR - Erliawan, Gusti Alvin; Firdaus, Muhammad (P3M Politeknik Negeri Banjarmasin, 2019)
Land is a very important basic material in a construction, because basically the soil serves as the object of all types of konstruki and as a base they saw on a structure must have the nature and power of a good support, ground the sand mixture is stabilized with 10% coconut fibres 1% ash, sand mix 10% ash 3% coconut fibers, sand mix 10% coconut fibres 5% ash. Research done in the laboratory of Geotechnical and Civil Engineering Transfortasi State Polytechnic Banjarmasin, testing is done at the programme LEVEL include: Testing water content in accordance with SNI 03-1965-2008, Heavy Type Testing in accordance with SNI 03-1964-2008, testing the limits of Liquid in accordance with SNI 03-1967-2008, testing the limits of Plastis accordance with SNI 03-1966-2008, Compaction Testing in accordance with STANDARD 03-1743-2008, and California Bearing Ratio Testing in accordance with STANDARD 03-1744-2012. From the results obtained by testing the value of the physical properties and mechanical ground on mixed 0%: 69.15% w, Gs 2.505, LL 49.50%, PL 31.64%, PI 13.61% 27.5% opt, w, Y d max 1.268 Gr/Cm3, CBR design 3.1%. From the results obtained by testing the value of the physical properties and mechanical Sand mixture soil at 10% Coconut Fibres 1% Ash: Gs (combined), 2.369 LL 49.55%, PL 33.18% PI, 16.37%, w opt 35.25%, Yd max 1.178 Gr/Cm3, CBR design of 6.8%. From the results obtained by testing the value of the physical properties and mechanical ground on mixed Sand Ash 10% 3% Coconut Fibres: Gs (combined), 2.369 LL 49.50%, PL 34.08% PI, 15.42%, w opt 25.50%, Yd max 1.205 Gr/Cm3, CBR design of 7.3%. From the results obtained by testing the value of the physical properties and mechanical Sand mixture soil at 10% Coconut Fibres 5% Grey: Gs (combined) 2.668, LL 49.40%, PL 35.79%, 13.61% PI, w opt 20.45%, Yd max 1.315 Gr/Cm3, CBR design 8.0%.